Movement patterns of Cape stumpnose, Rhabdosargus holubi (Sparidae), in the Kowie Estuary, South Africa - Grant, Gareth Neil (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2016)
Rhabdosargus holubi is an ubiquitous estuary-dependent fishery species endemic to southern Africa. Although aspects of its recruitment dynamics from sea to estuary have received considerable research attention, little is known about its movement behaviour within estuarine systems. Fishery surveys have also revealed that R. holubi is a dominant species in catches within several temperate estuaries in South Africa. Therefore, investigating movement behaviour is fundamental to understanding the ecology of this species and providing a means for implementing effective fisheries management strategies. This study made use of passive acoustic telemetry to quantify the movement patterns of juvenile R. holubi in the Kowie Estuary, in the Eastern Cape Province of South Africa. Previous studies have revealed that surgically implanted transmitters may have adverse effects on the physiology and behaviour of tagged fish. Therefore, due to the small size of juvenile R. holubi, an a priori transmitter-effect experiment was undertaken. This experiment revealed that juvenile R. holubi (146-217 mm fork length) were not adversely affected by the surgical implantation of acoustic transmitters (7 mm Ø, 1.6 g out of water) and hence acoustic telemetry was well suited to monitoring the movements of this species. A 4-month telemetry study evaluated the movement patterns of 21 juveniles (140-190 mm fork length) tagged in three equal batches along the length of the estuary. Specific aspects of their movement included space use patterns, habitat connectivity, and the influences of geophysical cycles and environmental variables. Tagged fish exhibited high residency, which varied between each release site area. The mean length of estuary used was greater for the upper batch (15.65 ± 6.49 km) than the middle and lower batches (7.36 ± 3.68 and 2.67 ± 2 km, respectively). In terms of habitat connectivity, once the tagged fish left the estuary, they generally did not return. Tagged R. holubi spent the majority (83%) of their monitoring periods within the estuarine environment, with the sea (16%) and riverine (1%) environments being utilised to a lesser extent. Diel and tidal cycles influenced the movement patterns of juvenile R. holubi. However, the high levels of residency meant that fine-scale movements were difficult to detect due to the acoustic receiver deployment configuration (i.e. receivers moored one kilometer apart). The influence of environmental variables on the movement of individuals, modelled with general linear mixed models (GLMMs), revealed that the effects of river inflow and water temperature were greatest. Increased river inflow caused individuals to use larger portions of the estuary. Increased water temperature, particularly river temperature, caused individuals to shift their distributions downstream (towards the mouth of the estuary). This study highlighted the importance of estuarine nursery habitats to R. holubi, suggesting that a loss or reduction of healthy estuarine habitats may lead to significant declines in the abundance of this species. Furthermore, extreme resident behaviour suggests that no-take area closures (estuarine protected areas) would be an effective management strategy for this important fishery species.
Keywords: Uncatalogued